2005
DOI: 10.1101/lm.95905
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of auditory fear conditioning after housing in a complex environment is attenuated by prior treatment with amphetamine

Abstract: Prior exposure to drugs of abuse has been shown to occlude the structural plasticity associated with living in a complex environment. Amphetamine treatment may also occlude some cognitive advantages normally associated with living in a complex environment. To test this hypothesis we examined the influence of prior exposure to amphetamine on fear conditioning in rats housed in either a standard or complex environment. Housing in a complex environment facilitated fear learning to an auditory conditioned stimulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
(25 reference statements)
1
9
1
Order By: Relevance
“…In all age groups, enrichment attenuated contextual freezing. Even if this result is inconsistent with previous studies showing that enrichment tended to increase contextual fear (Briand et al 2005;Duffy et al 2001;Tang et al 2001), we previously showed (Barbelivien et al 2006) that if, in adult rats, enrichment increased fear to a background context (i.e., when a tone perfectly predicts footshock occurrence), it concomitantly decreased fear to a foreground context (i.e., no predictive tone), as found in the current study at all ages. Therefore, the lower freezing scores that we observed in enriched rats may reflect a genuine decrease in fear rather than a deficit in contextual conditioning.…”
Section: Emotional Behaviorscontrasting
confidence: 99%
“…In all age groups, enrichment attenuated contextual freezing. Even if this result is inconsistent with previous studies showing that enrichment tended to increase contextual fear (Briand et al 2005;Duffy et al 2001;Tang et al 2001), we previously showed (Barbelivien et al 2006) that if, in adult rats, enrichment increased fear to a background context (i.e., when a tone perfectly predicts footshock occurrence), it concomitantly decreased fear to a foreground context (i.e., no predictive tone), as found in the current study at all ages. Therefore, the lower freezing scores that we observed in enriched rats may reflect a genuine decrease in fear rather than a deficit in contextual conditioning.…”
Section: Emotional Behaviorscontrasting
confidence: 99%
“…Furthermore, our results suggest that the neuroadaptations that resulted from repeated AMPH exposure, which are known to be associated with sensitization (Robinson and Berridge 2000), do not cause enduring deficits in the aspects of cognition that the delay-discounting task requires. It is not clear from the current study if the observed dissociation is specific to the dosing procedure used, but it is notable that previous studies using similar AMPH treatment schedules have reported a reduction in subsequent structural plasticity and forms of new learning (Kolb et al 2003;Briand et al 2005), as well as impairments in object recognition memory (Bisagno et al 2003;Belcher et al 2006).…”
Section: Discussionmentioning
confidence: 67%
“…It has been reported that low-dose amphetamine (10 mg, p.o., damphetamine, approximately 0.12 mg/kg for an 80 kg person) given during speech therapy, leads to improved recovery from aphasia (Walker-Batson et al 2001). In order to examine amphetamine's effects on experience-dependent plasticity in rats, researchers examined fear conditioning in rats housed in a complex environment for 3 months (Briand et al 2005). While rats showed enhanced learning after living in the complex environment, rats treated with damphetamine (4.0 mg/kg) for 21 days, then housed in the enriched environment for 3 months, did not show the same enhancement.…”
Section: Discussionmentioning
confidence: 99%